ANALISIS TEORI KEDATANGAN DAN PERKEMBANGAN ISLAM DI INDONESIA - Masruroh Lubis; Irwanto Irwanto; Rasyid Anwar Dalimunthe; Ruslan Efendi (STAI Asy-Syukriyyah, 2022)
The urgency of discussing the arrival and development of Islam, especially for students of Islamic education, is certainly something that should not be missed. The purpose of this discussion is to make it easier for Indonesia to understand the strong sources of its arrival and those influencing its development. This article was conducted through a literature study from literature, books and the internet. Then conduct a study related to the discussion. The result was the entry of Islam into Indonesia where Arab traders brought Islam by sea. Third, while a strong candidate as the first location for the entry of Islam to Indonesia is the coast of Sumatra. The four developments of Islam in Indonesia that became the main actors were the da'i and ustadz, ulama and several Islamic kingdoms. Fifth, along with its development, the life of Sufism and Islamic institutions emerged, including mosques, pesantren, surau and dayah.